Integrating STEAM with PjBL and PBL on biology education: Improving students’ cognitive learning results, creative thinking, and digital literacy - Wisye Hehakaya; Muhammad Nur Matdoan; Dominggus Rumahlatu (Universitas Negeri Jakarta, 2022)
STEAM (Science, Technology, Engineering, Art, and Mathematics) is an innovative interdisciplinary learning approach that can be integrated with PjBL and PBL learning models. This research investigates the effect of STEAM combined with PjBL and PBL learning models on the cognitive learning results, creative thinking skills and digital literacy of Class X senior high school students at SHS 3 Maluku Tengah and SHS 39 Salahutu. This research was conducted in the even semester of the 2020/2021 academic year. The research instruments included an essay test and digital literacy observation sheets. The research data were analyzed using inferential statistics (ANCOVA and ANOVA). The research results indicate that the integration of STEAM with PjBL and PBL learning models significantly affects students’ cognitive learning results and creative thinking (p<0.05). However, the integration of STEAM and PjBL and PBL learning models does not significantly affect students’ digital literacy (p>0.05). The integration of STEAM with PjBL and PBL learning models provides innovation in implementing the two learning models, which improves the learning steps and the learning process. The integration of STEAM with the PjBL learning model can be used to enhance cognitive learning outcomes and creative thinking skills for other biological concepts in senior high school level learning.